2022
DOI: 10.3332/ecancer.2022.1449
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related costs, the resulting financial impact and coping strategies among cancer survivors living in a setting with a pluralistic health system: a qualitative study

Abstract: Background: Evidence on the financial experiences of cancer survivors living in settings with pluralistic health systems remains limited. We explored the out-of-pocket costs, the resulting financial impact and the coping strategies adopted by cancer survivors in Malaysia, a middle-income country with a government-led tax-funded public health sector, and a predominantly for-profit private health sector. Methods: Data were derived from 20 focus group discussions that were conducted in five public and private Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Malaysia, Fnu et al [ 32 ] conducted a qualitative study that shed light on the considerable stress caused by the high costs associated with cancer treatments. As a coping mechanism, individuals sought financial assistance to alleviate the burden.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, Fnu et al [ 32 ] conducted a qualitative study that shed light on the considerable stress caused by the high costs associated with cancer treatments. As a coping mechanism, individuals sought financial assistance to alleviate the burden.…”
Section: Discussionmentioning
confidence: 99%
“…All these items cross-loaded with healthcare needs where it is likely that the items were highly correlated and complex [39]. The two domains that were excluded from EFA (diagnosis and employment) were retained in CFA due to their importance [18, 19,21] and expert justi cation [39]. It is noteworthy that the CFA indeed demonstrated that these two domains achieved adequate convergent and discriminant validity to justify their retention in the NeAT-CC.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of items was initially guided by ndings from independent qualitative inquiries that were previously undertaken by the study team in the local setting in people living with and beyond CRC. Details can be found elsewhere [18][19][20][21][22][23]. Concurrently, a literature review of the existing needs assessment tools for cancer was also conducted to screen for items [6][7][8][24][25][26].…”
Section: Item Generation and Domain Identi Cationmentioning
confidence: 99%